(untitled) (Medical Forum Monthly, 2024)
Objective: The present study was conducted to compare diagnostic validity of ultrasonography and fine needle aspiration cytology (FNAC) in thyroid gland swellings. Study Design: Observational study Place and Duration of Study: This study was conducted at the Department of Radiology Liaquat University of Medical and Health Sciences Jamshoro/Hyderabad and Department of Pathology Indus Medical College Tando Muhammad Khan, from April 2014 to September 2016 Materials and Methods: A sample of 100 thyroid patients was selected according to the inclusion criteria of age ≥ 20 years, and volunteers, new cases of thyroid neck swellings. Clinical examination was performed followed by sonography and FNAC with 23 G disposable syringe of 10 ml (BD, USA). Data was collected on a structured proforma. Software SPSS 22.0 version (IBM, incorporation, USA) was used for data analysis at 95% Confidence interval (P≤0.05). Results: Mean ±SD age of study subjects was 49.7±11.5 years. 63% were female and 37% male subjects (p=0.0001). Overall sensitivity, and specificity, PPV and NPV of sonography in identifying malignant thyroid lesions was 69%, 87%, 56% and 58% respectively. Conclusion: The present study shows thyroid sonography is an extremely useful non-invasive test for ruling out the malignant lesions when combined with FNAC.